Identification of the key morphological sweetpotato weevilresistance predictors in Ugandan sweetpotato genotypes usingcorrelation and path-coefficient analysis - Osaru, F.; Karungi, J.; Odama, R.; Chelangat, D.M.; Musana, P.; Otema, M.A.; Oloka, B.M.; Gibson, P.; Edema, R.; Ssali, R.T.; Yencho, George Craig; Yada, B. (Wiley, 2023)
Sweetpotato weevils (SPWs) can cause up to 100% yield losses in sweetpotato (Ipomoea batatas). Nevertheless, there has been limited success in breeding for SPW resistance globally. This is attributed partly to difficulty in screening for resistance because resistance to the SPW is complex and is mediated by several resistance indicators. Measuring all these resistance indicators is costly and time consuming. To enhance efficiency in selection for SPW resistance, there is need to profile and identify key resistance indicators. Potentially, this will better enable breeders to timely and precisely select for SPW resistance. The objective of this study was to identify the most efficient morphological resistance indicators against SPW. Thirty sweetpotato genotypes that varied in resistance to SPW comprising local collections, released varieties, and breeding lines were evaluated at three locations for two seasons in Uganda using an alpha lattice design. Data were collected on storage root yield, SPW root and stem damage, and weevil resistance indicators such as vine vigor (VV), ground cover (GC), vine weight (VW), storage root neck length (NL), latex content, cortex thickness (CT), and dry matter content (DM). Genotype means for all measured traits varied significantly except for CT. Negative relationships were observed between SPW root damage and GC, VW, CT, VV, NL, and DM. However, path coefficient analysis showed storage root NL (direct effect of −0.43, p < 0.001) as the most important morphological resistance indicator. Therefore, NL could be the most reliable predictor of resistance to SPW among breeding clones, especially at early breeding stages.